Current approaches to the selection of acetylsalicylic acid dosage forms in cardiology - S. R. Gilyarevskiy; M. V. Golshmid; N. G. Bendeliani; I. M. Kuzmina («REMEDIUM GROUP» Ltd., 2022)
The article is devoted to modern approaches to the selection of optimal dosage forms of acetylsalicylic acid (ASA), which ensure high bioavailability of ASA drugs. The relevance of improving the tactics of ASA use for both primary and secondary prevention of cardiovascular diseases is discussed. Changes in the role of ASA in the prevention of cardiovascular disease complications are discussed, including as part of combined antithrombotic therapy, including ASA and either P2Y12 inhibitor or low-dose rivaroxaban. Evidence is presented that has led to doubts about the sufficient bioavailability of the enteric form of ASA, as well as the predictability of the response to therapy. A separate part of the article is devoted to the safety of different forms of ASA, in particular - the effect on the mucosa of the small intestine. The results of clinical studies evaluating the effect of ASA intake in enteric-soluble and buffered forms on the small intestinal mucosa and the risk of bleeding are presented. In addition, the problem of decreased effectiveness of ASA intake in overweight or obese individuals is considered. The article provides information on ongoing randomized trials to assess the effectiveness of increasing the frequency of ASA intake, as well as the effectiveness of chronopharmacological approaches to optimize the use of ASA. The analysis performed leads it to conclude that the buffer form can now be considered the preferred acetylsalicylic acid (ASA) dosage form, which, on the one hand, exerts a less pronounced effect on the gastric and small intestinal mucosa, and on the other hand, ensures high bioavailability, as well as minimal variability of treatment response.